PERBANDINGAN MODEL PENDEKATAN TAKTIS DAN MODEL PEMBELAJARAN KOOPERATIF TERHADAP JUMLAH WAKTU AKTIF BELAJAR (JWAB) DALAM PEMBELAJARAN PERMAINAN BOLABASKET - Fahri, Muhammad Hasbiyal; Juliantine, Tite (STKIP Pasundan, 2016)
The purpose of this study was to determine the effect of tactical approach models and cooperative learning models on the amount of active learning time (JWAB) students in learning basketball games. The research method used is the experimental method. The population in this study were 300 students and a sample of 40 students. Sampling using a purposive sampling technique. The research design uses one group pretest-posttest design. The research instrument in this study used the physical teaching performance assessment instrument. Raw data shows an average difference between the tactical approach model group and the cooperative learning model group to the amount of active learning time. The results of data processing and hypothesis testing show an increase in the amount of active learning time for students of SMP Negeri 1 Plered. From the results of data processing and analysis, it can be concluded that the tactical approach model gives a more significant effect compared to the cooperative learning model on the amount of active learning time in Plered 1 Junior High School.